Use of {99m}Tc-HMPAO in Evaluating the Results of Cerebral Hypoperfusion Prevention in the Patients with Coronary Heart Disease after Coronary Artery Bypass Grafting; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Efimova N. Yu. Nataliya Yurievna; Chernov V. I. Vladimir Ivanovich; Efimova I. Y.; Akhmedov S. D.; Lishmanov Yu. B. Yury Borisovich (Radiation Technologies in Medicine, 2015)
Title screen